2015
DOI: 10.1186/s13058-015-0589-9
|View full text |Cite
|
Sign up to set email alerts
|

CD24+ cells fuel rapid tumor growth and display high metastatic capacity

Abstract: IntroductionBreast tumors are comprised of distinct cancer cell populations which differ in their tumorigenic and metastatic capacity. Characterization of cell surface markers enables investigators to distinguish between cancer stem cells and their counterparts. CD24 is a well-known cell surface marker for mammary epithelial cells isolation, recently it was suggested as a potential prognostic marker in a wide variety of malignancies. Here, we demonstrate that CD24+ cells create intra-tumor heterogeneity, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…Screening antibody molecules that take into account stem‐like cells and cancer cells should be one of the directions for future research on immunity . Thus, our screening methods were not only based on the affinity to the microspheres but also dependent on the selective effect on their early differentiated cells . This approach ensured that subsequent identification and treatment was effective both for the microspheres and cancer cells (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening antibody molecules that take into account stem‐like cells and cancer cells should be one of the directions for future research on immunity . Thus, our screening methods were not only based on the affinity to the microspheres but also dependent on the selective effect on their early differentiated cells . This approach ensured that subsequent identification and treatment was effective both for the microspheres and cancer cells (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…18 However, CD24 + cells are considered more closely related to the early, highly invasive, and differentiated cells in mammary tumors. 17,19 We infer that CSCs themselves may always be in a dynamic balance and inhomogeneous collective state. As Reya et al 20 have suggested, cancer cells, stem cells, and CSCs may share a common signaling pathway.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In particular, Gay et al (2016) [42] analyzed and summarized in their review more than 30 publications concerning cellular heterogeneity of various malignant tumors (kidney, lung, colon, mammary gland, prostate, ovary, etc.). The genetic, epigenetic, and phenotypic mechanisms of intra-tumor cell heterogeneity have been described [42,46,47] . Traditionally tumor cell heterogeneity was explained with a clonal selection and adaptation models.…”
Section: Modern Biochemistry and Post-genomic Technologies In Researcmentioning
confidence: 99%
“…For example, Moghbeli et al (2014) [52] introduced different protocols used to isolate CSCs from solid tumors of colon, esophagus, liver, breast, brain, and cervix. The isolation of CSCs can be accomplished by selection of tumor cell subpopulations based on expression of one or more of cell surface markers associated with cancer self-renewal such as: CD133, CD166, CD44, CD24, beta1 integrin-CD29 and others [47,53] . The alternative hypothesis suggested that tumor growth could be mediated, at least in part, by the coalescence of multiple tumorigenic foci within a tissue, a process that would contribute to tumor heterogeneity [40,46,[54][55][56] .…”
Section: Modern Biochemistry and Post-genomic Technologies In Researcmentioning
confidence: 99%